Sistem deteksi kebocoran gas lpg berbasis internet of things: Implementation of the internet of things for LPG gas leak detection system - Aisa, Sitti; Husain; Alif Al Qadri (Universitas Muhammadiyah Riau, 2026)
LPG gas has become a primary household necessity due to its cost-effectiveness and ease of use. However, the risk of gas leaks, which can lead to fires, remains a significant drawback, primarily due to a lack of public awareness of how to mitigate them. This research aims to design and build a prototype of an integrated Internet of Things (IoT)-based security system for early detection and mitigation of gas leaks. The system uses two MQ-5 gas sensors to monitor gas concentrations in two different areas and two infrared (IR) sensors to control automatic door access. Data from the sensors is acquired by an ESP8266 microcontroller, which then sends it wirelessly to a server for processing. The system provides a multi-layered response: early warning via buzzer, real-time data visualization on a web dashboard, and instant notifications to users via Telegram. Test results show the system has a reasonable response, where the MQ-5 sensor is able to detect gas and process it on the server in approximately 20 seconds, and the infrared sensor accurately detects objects with 95% accuracy. With the implementation of IoT technology, the system is not only able to continuously monitor gas concentrations in the air, but also provide automatic response actions, thereby increasing alertness and significantly reducing the risk of fires due to gas leaks.